Transition Metals Based Anti-Alzheimer - Ambarita, Theresia; Pasaribu, Cinta Johanna Tessalonika (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2023)
Alzheimer's disease (AD), a progressive neurodegenerative disease, is the most common cause of dementia. Amyloid-B protein’s accumulation in amyloid plaques, oxidative stress, tau protein phosphorylation, poor energetics, mitochondrial dysfunction, membrane lipid dysregulation, inflammation, and neurotransmitter pathway disruption, play a part in the pathophysiology of Alzheimer's disease. AD is primarily characterized by the formation of amyloid-B aggregates. Transition metal complexes have recently been produced as chemical reagents for modifying AB aggregation. Transition metal complexes have tunable features such as the metal center's oxidation and spin states, as well as its coordination structure by altering the ligand bound to the metal center. These variable properties result in the reactivity of transition metal complexes with AB species and may lead to the regulation of the AB aggregation pathway. The purpose of this study is to describe the application of transition metals as active compounds in anti-Alzheimer's disease drugs. This study was compiled from online journals using secondary data searched by keyword. The results of the study show that some transition metals have potential therapeutic effects for AD. Ru can be an AB aggregation inhibition. Fe, Cu, and Zn transition metals are necessary for human survival and involved in AD triggering. Pt, Ni, Co, and V complexes play a role as multifunctional therapeutic agents against AD. This literature review includes a recently published (year>2000) report on the role of transition metals as anti-Alzheimer's.